Kinetics of decomposition of Tert-butyl peroxyisobutyrate during vulcanisation of natural rubber latex - Mazam Md Said; Blackley D C; Pendle T D (Journal of Natural Rubber Research, 1991)
The development of a modified iodometric method of estimating the concentration of tert-butyl peroxyisobutyrate (tBPIB) in natural rubber (NR) latex is described. The decomposition of tBPIB in NR latex, in the presence or absence of fructose was found to be a first-order reaction with respect to tBPIB concentration. The initial rate of tBPIB decomposition, however, was found to be half order with respect to initial tBPIB concentration. The effect of reaction variables on the rate of tBPIB decomposition is discussed. The activation parameters are calculated from the rate measurements. The significance of the kinetics of decomposition in relation to tBPIB reaction and the kinetics of crosslinking is discussed.
Keywords: NR latex; Tert-butyl peroxyisobutyrate